2023
DOI: 10.1161/circep.122.011677
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Repolarization and Cell-Cell Variability of Cardiomyocyte Remodeling Within the Myocardial Infarction Border Zone Contribute to Arrhythmia Susceptibility

Abstract: BACKGROUND: After myocardial infarction, the infarct border zone (BZ) is the dominant source of life-threatening arrhythmias, where fibrosis and abnormal repolarization create a substrate for reentry. We examined whether repolarization abnormalities are heterogeneous within the BZ in vivo and could be related to heterogeneous cardiomyocyte remodeling. METHODS: Myocardial infarction was induced in domestic pigs by 120-minute ischemia-reperfusion injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The elevated RTG caused the lines of conduction block to be longer, resulting in larger reentrant circuits. This, in combination with the lowered CV T in the remote part of reentrant pathways, can prolong reentrant cycle time and more easily result in sustained VT. Those effects might be even more pronounced if cardiomyocyte and APD heterogeneity after infarction is caused by mechanical load as well, as suggested in recent work ( Amoni et al, 2023 ).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The elevated RTG caused the lines of conduction block to be longer, resulting in larger reentrant circuits. This, in combination with the lowered CV T in the remote part of reentrant pathways, can prolong reentrant cycle time and more easily result in sustained VT. Those effects might be even more pronounced if cardiomyocyte and APD heterogeneity after infarction is caused by mechanical load as well, as suggested in recent work ( Amoni et al, 2023 ).…”
Section: Discussionmentioning
confidence: 57%
“…Frontiers in Physiology frontiersin.org 10 sustained VT. Those effects might be even more pronounced if cardiomyocyte and APD heterogeneity after infarction is caused by mechanical load as well, as suggested in recent work (Amoni et al, 2023).…”
Section: Tissue Heterogeneity and Vt Riskmentioning
confidence: 61%
“…MSC injections into the ventricular myocardium after MI have resulted in reverse-remodeling of the myocardium and improvement in ventricular function [ 9 ], however, its effect on ischemic ventricular arrhythmia has not been clearly demonstrated. The scar border zone is the main environment susceptible for post-MI VT, and the direct injection of stem cells into this area would be more effective for improving electrophysiologic properties than the stem cell implantation in infarcted myocardium with a non-viable scar [ 10 ]. However, results of experimental studies indicated that MSC therapy could be proarrhythmic due to altered electrophysiologic properties that can result in slowed conduction velocity and the changes in substrate refractoriness in MSC-survived heart tissue [ 11 ].…”
Section: Introductionmentioning
confidence: 99%